Sensitivity of physiological and biochemical endpoints in early ontogenetic stages of crops under diclofenac and paracetamol treatments - Zezulka, Štěpán; Kummerová, Marie; Babula, Petr; Hájková, Markéta; Oravec, Michal (Environmental science and pollution research international, 2019)
Early stages of ontogenesis determining subsequent growth, development, and productivity of crops can be affected by wastewater and sludge contaminated with pharmaceuticals. Diclofenac (DCF) and paracetamol (PCT; both 0.0001 to 10 mg/L) did not affect seed germination and primary root length of onion, lettuce, pea, and tomato. Conversely, 20-day-old pea and maize plants exhibited decrease in biomass production, leaf area (by approx. 40% in pea and 70% in maize under 10 mg/L DCF), or content of photosynthetic pigments (by 10% and 60% under 10 mg/L PCT). Quantum yields of photosystem II were reduced only in maize (FV/FM and ΦII by more than 40% under 10 mg/L of both pharmaceuticals). Contents of H2O2 and superoxide increased in roots of both species (more than four times under 10 mg/L PCT in pea). Activities of antioxidant enzymes were elevated in pea under DCF treatments, but decreased in maize under both pharmaceuticals. Oxidative injury of root cells expressed as lowered oxidoreductase activity (MTT assay, by 40% in pea and 80% in maize) and increase in malondialdehyde content (by 60% and 100%) together with the membrane integrity disruption (higher Evans Blue accumulation, by 100% in pea and 300% in maize) confirmed higher sensitivity of maize as a C4 monocot plant to both pharmaceuticals.
Keywords: Content of pharmaceuticals; Waste Water; diklofenak; Malondialdehyde; odpadní voda; Nonsteroidal anti-inflammatory drugs; Antioxidants; malondialdehyd; Crop plants; Plant Leaves; Seeds; peroxid vodíku; Plant Roots; chemické látky znečišťující vodu; fotosyntéza; antioxidancia; zemědělské plodiny; kořeny rostlin; semena rostlinná; Crops, Agricultural; Acetaminophen; Water Pollutants, Chemical; Growth; klíčení; Photosynthesis; Wastewater; Germination; Diclofenac; paracetamol; Hydrogen Peroxide; listy rostlin; Oxidative stress